Applications of photogrammetry to orthodontics - Thomann John Von; Rivett Leo J. (Sciendo, 1982)
An investigation was conducted into the potential of utilizing standardized photogrammetry techniques to evaluate facial soft tissue morphology. A head holding device was used to provide a standardized reference system and the accuracy of repositioning for a second photographic recording was evaluated. Three dimensional co-ordinates of points on the facial surface were derived by analytical photogrammetry procedures from stereo photographs acquired via a pair of stereometrie cameras. These points were manipulated via computer programs to provide frontal and horizontal face contour plots. Quantitative volume measurements determined from the skin surface to a constructed datum plane provided assessment of facial asymmetry across a constructed reproducible frontal midline, the perpendicular bisector of the interpupillary line. Photogrammetry was found to be a versatile, non-contact and precise three-dimensional recording method, with potential application to basie research and to the clinical management of orthodontic and oral surgery patients.